Adsorption performances and electrochemical characteristics of methyl blue onto magnesium-zinc ferrites. (7th January 2022) - Xu, Shuping; Liu, Dandan; Liu, Aihua; Sun, Fu; Pan, Shengying; Ouyang, Hezhong
Abstract: A novel and facile rapid combustion approach was developed for the controllable preparation of small size and easy recovery magnesium-zinc ferrites for methyl blue (MB) removal in dye solution. The effects of prepared criteria of x value, calcination temperature, and the amount of ethanol on the average grain sizes and magnetic property were reviewed. The characterization results displayed that Mg0.5 Zn0.5 Fe2 O4 nanoparticles met the expectations of the experiment at the calcination temperature of 400 °C with absolute ethanol volume of 20 ml, and they were selected to remove MB. The adsorption process belonged to chemical adsorption on the basis of the pseudo-second-order model. The electrochemical characteristics of MB onto the prepared nanoparticles were analyzed by cyclic voltammetry (CV). The influences of pH and cycle times on the removal efficiency were investigated. When the pH went beyond 3, the removal efficiency of MB onto the magnetic Mg0.5 Zn0.5 Fe2 O4 nanoparticles maintained above 99%, the maximum adsorption capacity was 318.18 mg g −1 . After seven cycles, the relative removal rate of MB remained 96% of the first one.